Electrodeposition of Lithium-Silicon Alloys from 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)amide. Issue 16 (29th November 2018) - Pulletikurthi, Giridhar; Olschewski, Mark; Endres, Frank
Abstract : The codeposition of lithium and silicon was investigated from 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)amide ([Py1, 4 ]TFSA) at temperatures ≥ 100°C. Furthermore, electrodeposition of lithium was studied from the same liquid at ≥ 100°C. Two different sources of Si(IV) (e.g. either SiCl4 or SiBr4 ) and LiTFSA as a source for Li + ions were used. Cyclic voltammetry was employed to study the electrochemical behavior of (SiCl4 +LiTFSA)/[Py1, 4 ]TFSA and (SiBr4 +LiTFSA)/[Py1, 4 ]TFSA. The electrodeposited films were characterized using Scanning Electron Microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy. SiBr4 was found to be suitable to obtain Li-Si alloys from the mentioned IL. Nanocrystalline lithium was obtained with an average grain size of 30 to 40 nm. XRD analysis of the annealed deposits revealed the formation Li-Si alloys. XPS analysis of the deposit obtained from (SiBr4 +LiTFSA)/[Py1, 4 ]TFSA indicated the presence of fluoride and oxide of lithium besides metallic lithium.